1994
DOI: 10.1111/j.1545-5300.1994.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Perceptions of Living with Alzheimer's Disease

Abstract: The purpose of this study was to identify the major themes that 38 multigenerational families emphasized in their conversations about living with Alzheimer's disease. Interviews were conducted with families that were providing home care in the early stages of the disease. Family perceptions were analyzed with the aid of a computer content analysis program. Families emphasized four themes: (a) the awareness that something was "wrong"; (b) the uncertain nature of the diagnosis; (c) excluding a family member; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…/-Icuristic e-scores suggest the overall character of ideas that are emphasized in the text (McTavish & Pirro, 1990;Garwick, Detzner, & Boss, 1994). The top ten e-scores suggested visitor meanings and their on-site experiences.…”
Section: Figure 1 Emphasis Scores Of Pre and Post Groups On All Thrementioning
confidence: 99%
“…/-Icuristic e-scores suggest the overall character of ideas that are emphasized in the text (McTavish & Pirro, 1990;Garwick, Detzner, & Boss, 1994). The top ten e-scores suggested visitor meanings and their on-site experiences.…”
Section: Figure 1 Emphasis Scores Of Pre and Post Groups On All Thrementioning
confidence: 99%
“…Cohen-Mans®eld and Werner (1998) conducted a methodologically solid study of the eects of environmental manipulation, but applied this intervention to all participants without consideration of individual dierences. Although Goldsmith et al (1995) and Okawa et al (1991) provided evidence that systemic interventions such as increased social interaction between residents and sta could decrease resident wandering, the sta training procedures were not adequately described in these studies, rendering it dicult for other researchers to replicate the intervention.…”
Section: Wanderingmentioning
confidence: 92%
“…Goldsmith et al (1995) found that increasing the amount of time sta spend interacting with residents reduces wandering behavior. Similarly, Okawa et al (1991) have shown that increasing social interaction with nurses is eective in reducing wandering in 30% of dementia patients showing these problems.…”
Section: Wanderingmentioning
confidence: 98%
See 2 more Smart Citations